The magician and the spirits Harry Houdini and the curious pastime of communicating with the dead - Noyes, Deborah 1965- (Viking, 2017)
"Famed illusionist Harry Houdini embarks on a quest to investigate spiritual phenomena and the possibility of communication with those on the "other side.""...